A new approach for subcontractor selection in the construction industry based on portfolio theory - Abbasianjahromi, Hamidreza; Rajaie, Hossein; Shakeri, Eghbal; Kazemi, Omid (Journal of Civil Engineering and Management, 2016)
Various challenges such as new technologies, growing complexity and competitive environment, require the main contractor to assign some of the project’s tasks to other parties, the so-called subcontractors. Although subcontracting is a usual phenomenon in the construction industry, insufficient attention to the subcontractor selection strategy may pose some major threats to a project. Having in mind the significance of such risks, the optimization of subcontractor selection is essential for the success of the project. The importance of risk management in selecting subcontractors and the direct relation between risks and returns in most projects are two main motives for using the concept of portfolio in this paper. The main objective of this paper is to propose a model to allocate the best portion of project’s task to some subcontractors in order to reach the optimized portfolio of subcontractors and main contractor. This is a new approach in the subcontractor management; therefore, after presenting the model, an illustrative example will be presented for better understanding.